Analysis of real time PCR amplification efficiencies from three genomic region of dengue virus. - Odreman Macchioli, María; Vielma, Silvana; Atchley, Daniel; Comacho, Guillermo; Ramirez, Alvaro; Pérez, Saberio; Téllez, Luis; Quintero, Beatriz; Hernández, Erick; Muñoz, Maritza; Mendoza, José (Investigación Clínica, 2013)
Early diagnosis of dengue virus (DENV) infection represents a key factor in preventing clinical complications attributed to the disease. The aim of this study was to evaluate the amplification efficiencies of an in-house quantitative real time-PCR (qPCR) assay of DENV, using the non-structural conserved genomic region protein-5 (NS5) versus two genomic regions usually employed for virus detection, the capsid/pre-membrane region (C-prM) and the 3”™-noncoding region (3”™NC). One-hundred sixty seven acute phase serum samples from febrile patients were used for validation purposes. Results showed that the three genomic regions had similar amplification profiles and correlation coefficients (0.987-0.999). When isolated viruses were used, the NS5 region had the highest qPCR efficiencies for the four serotypes (98-100%). Amplification from acute serum samples showed that 41.1% (67/167) were positive for the universal assay by at least two of the selected genomic regions. The agreement rates between NS5/C-prM and NS5/3”™NC regions were 56.7% and 97%, respectively. Amplification concordance values be- tween C-prM/NS5 and NS5/3”™NC regions showed a weak (K= 0.109; CI 95%) and a moderate (K= 0.489; CI 95%) efficiencies in amplification, respectively. Serotyping assay using a singleplex NS5-TaqMan® format was much more sensitive than the C-prM/SYBR Green® I protocol (76%). External evaluation showed a high sensitivity (100%), specificity (78%) and high agreement between the assays. According to the results, the NS5 genomic region provides the best genomic region for optimal detection and typification of DENV in clinical samples.